GEMINI Y SU APORTE EN EL APRENDIZAJE DE LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGÍA DE LAS CIENCIAS EXPERIMENTALES INFORMÁTICA, DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO, PERIODO ACADÉMICO ABRIL-AGOSTO 2024. - MATA BURGOS KATERINE DEL ROCIO (2024)
The general objective of the Curricular Integration Work is to analyze the contribution of Gemini artificial intelligence as a research tool in the students of the Pedagogy of Experimental Sciences and Computer Sciences at the Technical University of Babahoyo. The specific objectives include identifying the characteristics of Gemini in the students' learning process, as well as its importance and estimation of the acceptability that Gemini contributes as a result to student learning and research. It is hypothesized that Gemini will significantly influence student learning. The background and theoretical contribution are identified, based on the compilation obtained from scientific journals, books, among others. In the methodology, the type and design of the research is detailed, using a mixed approach, applying the qualitative and quantitative method, and it is specified that the work is descriptive and documentary research. The study population consists of 396 students, who were asked a questionnaire with ten closed questions using the survey as a data collection technique. Finally, based on the results obtained, it was concluded that artificial intelligence contributes significantly to the learning process of PCEI career students.